2021
DOI: 10.1007/s11104-021-04881-5
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground litter inputs determine carbon storage across soil profiles: a meta-analysis

Abstract: Aims Aboveground plant litter inputs are important sources of soil carbon (C). We aimed to establish how experimentally altered litter inputs affect soil C to 1-m depth across different ecosystems, and over different timeframes. MethodsWe performed a meta-analysis of 237 studies across 248 sites worldwide to assess the influence of treatment magnitude, treatment duration, initial soil C content, and climate on the response of soil C to altered aboveground litter inputs. ResultsOverall, soil C content was lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 89 publications
3
17
0
Order By: Relevance
“…These results suggest that, without exogenous C inputs from plants, microbial decomposition of SOM will cause continuous loss of soil C, especially in the long term (Figure 6; Figure S9; Dove et al, 2019). Under litter addition, the response of SOC showed a significant increasing trend with duration ( p = .029), in accordance with a previous meta‐analysis (Xu et al, 2021). However, duration had a limited explanation for the variations in SOC responses ( R 2 = .046), particularly when the data with the longest duration were excluded from the regression analysis ( R 2 = .011; Figure S9).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results suggest that, without exogenous C inputs from plants, microbial decomposition of SOM will cause continuous loss of soil C, especially in the long term (Figure 6; Figure S9; Dove et al, 2019). Under litter addition, the response of SOC showed a significant increasing trend with duration ( p = .029), in accordance with a previous meta‐analysis (Xu et al, 2021). However, duration had a limited explanation for the variations in SOC responses ( R 2 = .046), particularly when the data with the longest duration were excluded from the regression analysis ( R 2 = .011; Figure S9).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to litter input rate, the initial SOC in the DIRT network experiments is much higher (58 g kg −1 vs. 41 g kg −1 ; Table S5), which, thus, may lead to a relatively small response of SOC to litter addition. Alternatively, soils with high initial SOC may have a limited capacity to sequester additional C (Xu et al, 2021). The overall significant positive response of SOC pool to litter addition in our present study suggested that aboveground litter inputs can cause a net increase in SOC storage despite the litter‐induced priming (5.3%) of native SOM decomposition (Figure S8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The species were organized in different groups, where C. tomentosum is more associated with d 13 Xu et al 2021). Due to the relatively short time after pasture conversion to the N-xing stands, the soil C and N in the subsoil are probably derived from the forest vegetation even before the pasture.…”
Section: Soil 13 C and 15 N Abundance Uctuationsmentioning
confidence: 99%
“…In recent decades, forest litter and net primary productivity are altered by global environmental changes, such as increasing atmospheric carbon dioxide concentrations (Song et al 2019), warming (Li et al 2017;Quan et al 2019) (Huang et al 2016), and atmospheric nitrogen deposition (Du et al 2019;He et al 2021). Variation in litter inputs to soil would impact the amount of C and nutrients entering the soil system and thus the amount of C and nutrients internally cycled in forest plantations (Huang and Spohn 2015;Sayer et al 2011;Sayer et al 2020;Xu et al 2021 ). This impact can feedback to tree growth and exert profound effects on plant productivity and litter production.…”
Section: Introductionmentioning
confidence: 99%